PERAN DIMENSI HUMAN CAPITAL TERHADAP KINERJA TENAGA PENDIDIK DI SDN.3 PENANCANGAN DI KOTA SERANG - Ahmadi, Ahmadi; vera maria; suherman, suherman (Bajang Institute, 2024)
This study examines the role of human capital dimensions on the performance of educators in SDN 3 Penancangan, Serang City. Human capital is crucial in enhancing educational outcomes, particularly in primary schools where foundational learning takes place. This research focuses on four main dimensions of human capital: education, experience, skills, and motivation. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive data. Findings indicate a significant correlation between educators' human capital dimensions and their performance levels. Educational attainment and professional experience emerged as pivotal factors contributing to effective teaching practices. Furthermore, the study highlights the importance of continuous professional development and motivational strategies in sustaining educator performance. The implications of these findings underscore the necessity for targeted policies and interventions to enhance human capital among educators, thereby improving overall educational quality in primary schools.